Effects of polymerization time towards conductivity and properties of poly(methyl methacrylate)/polyaniline (PMMA/PANi) copolymer - Abu Hassan Shaari, Helyati; Ramli, Muhammad Mahyiddin; Abdullah, Mohd Mustafa Al Bakri; Mohtar, Mohd Nazim; Abdul Rahman, Norizah; Ahmad, Azizan; Osman, Nurul Huda; Rusydi, Febdian (Multidisciplinary Digital Publishing Institute, 2022)
The effects of various polymerization times on the properties and conductivity of poly(methyl methacrylate)/polyaniline (PMMA/PANi) copolymer has been investigated. Different polymerization times, such as 1 h, 2 h, and 3 h, have been employed during free radical copolymerization of PMMA/PANi copolymer. The properties of newly synthesized PMMA/PANi copolymer were discussed with the help of Fourier transform infrared (FTIR), 1H nuclear magnetic resonance (NMR) spectroscopies, UV-Vis spectroscopy, and transmission electron microscopy. All copolymers showed electrical conductivity of a semi-conductor material, compared with PMMA itself. It was found that the reaction played a significant role, especially at optimum polymerization time, where PANi formation and conductivity was at its highest. Our present work demonstrates that copolymer film could be a promising material to fabricate polymer conducting film in many electronics applications.